2013
DOI: 10.1016/j.repc.2012.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Congestive heart failure as a determinant of postoperative delirium

Abstract: Patients who developed POD had longer hospital and PACU stays and higher in-hospital mortality. Congestive heart disease was considered an independent risk factor for POD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Systemic inflammatory response and increased need for blood transfusions have been determined to be independent risk factors and could be strongly tied to length of surgery [16,18,33]. Furthermore, the length of time spent under mechanical ventilation is correlated with both duration of surgery and of anesthesia, due to longer procedures requiring prolonged mechanical ventilation [18,34]. As previously discussed, complex surgeries have many risk factors for POD, and prolonged intubation is another component to consider.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Systemic inflammatory response and increased need for blood transfusions have been determined to be independent risk factors and could be strongly tied to length of surgery [16,18,33]. Furthermore, the length of time spent under mechanical ventilation is correlated with both duration of surgery and of anesthesia, due to longer procedures requiring prolonged mechanical ventilation [18,34]. As previously discussed, complex surgeries have many risk factors for POD, and prolonged intubation is another component to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Another very strong risk factor is a decrease in blood proteins, with both studies investigating this factor finding a correlation coefficient below 0.005 [23,31]. A decreased RBC count is a strong risk factor for delirium with two articles demonstrating a highly significant correlation between a decrease in RBC and delirium [31,34]. Elevated creatinine levels are a strong risk factor for delirium with nine of twelve studies finding it significant [16,23,27,28,32,33,35] (Table 4).…”
Section: Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…37,38,39,40 Delirium, a common sequela of decompensated HF, is associated with prolonged hospital stays and increased mortality. 41 Disease management programmes and aerobic exercise seem to be as effective as drug therapy, 55 and repeated visits from nurses and routine contact calls from healthcare staff to give education and care support were found to reduce hospital readmissions and increase quality of life. 56…”
Section: Several Risk Factors For Stroke In Patients With Hf Have Beementioning
confidence: 99%
“…10 Another study found that heart disease was a risk factor. 11 Risk factors of delirium in outpatients have been studied in just a few studies. These studies reported that infections, stressful events, surgery, medical illnesses, heart failure, metabolic-endocrine disturbances, and the use of medication like benzodiapines and haldoperidol, as well as polypharmacy were associated with an increased risk of prevalent delirium.…”
mentioning
confidence: 99%